Critical mass of Engineering in health care - Jarzembski, W. B. (Revista Mexicana de Ingenieria Biomedica, 2018)
The development of engineering in the past ten years has given health centers the technology that was only dreamed ten years ago. Unfortunately, the engineering activities in these health centers have not progressed, and in several institutions for health care they do not even recognize the problems caused by this lack of engineering aspects. These problems include less than optimal patient care and extremely high costs for health care. The present work is directed towards the growth of technology dedicated to health care. Long-term and short-term approaches to solve this problem are also discussed here.